2014
DOI: 10.2514/1.c032377
|View full text |Cite
|
Sign up to set email alerts
|

Inspection Intervals Optimization for Aircraft Composite Structures Considering Dent Damage

Abstract: Many probability techniques have been proposed, but the inspection intervals for composite structures have not been comprehensively addressed. The present study focuses on the most frequent damage type, dent, and uses probabilistic approaches to analyze statistical characteristics of the damage based on maintenance data from a Chinese airline. Dent sizes are considered from three dimensions: the damage diameter, the damage depth, and the diameter/depth ratio. The life-cycle strength of a composite structure is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…Studies on inspection accuracies within the aviation domain presented detection rates of 68% for the visual inspection of aircraft fuselage [ 32 ], 42% in cargo bay inspection [ 33 ], and 57–98% for the magnetic particle inspection of landing gear components [ 34 ]. The main focus in this industry is on crack and dent detection, predominantly in composite materials, and thus inspection results are commonly reported as probability of detection (PoD) curves, i.e., the chance of defect detection depending on the defect size [ 23 , 24 , 25 , 26 , 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on inspection accuracies within the aviation domain presented detection rates of 68% for the visual inspection of aircraft fuselage [ 32 ], 42% in cargo bay inspection [ 33 ], and 57–98% for the magnetic particle inspection of landing gear components [ 34 ]. The main focus in this industry is on crack and dent detection, predominantly in composite materials, and thus inspection results are commonly reported as probability of detection (PoD) curves, i.e., the chance of defect detection depending on the defect size [ 23 , 24 , 25 , 26 , 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Not all studies reported a specific detection rate, since it is dependent on the defect type and size. Hence, for cracks and dents-the most common defects investigated in previous studies-the results were commonly reported as probability of detection (PoD) curves, which visualises the likelihood of detecting the defect (y-axis) as a function of the defect size (x-axis) [14][15][16][17][18]. For such PoD curves, a minimum sample size of N = 60 per defect type is required [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…PMT has initially used in assessing health risk behaviours which later has been applied widely in other fields as well particularly related to the study of pro-environmental behaviours. The Protection Motivation Theory [34] is shown in the Figure 3 clearly demonstrates the context, constructs and the resultant behaviour. The new Corona Virus which was initially named as Novel Corona Virus emerged in Wuhan, China in December 2019.…”
Section: Fig 2 Green It Life Cyclementioning
confidence: 99%